Evaluation of the mechanical properties of different materials for manufacturing occlusal splints - Guimaraes, Danielly Mendonça; Campaner, Marcio [UNESP]; dos Santos, Rodrigo Wendel; Pesqueira, Aldiéris Alves [UNESP]; de Medeiros, Rodrigo Antonio (FapUNIFESP (SciELO), 2023)
This study aimed to compare the mechanical properties of various occlusal plate materials by analyzing surface roughness, Knoop microhardness, flexural strength, and modulus of elasticity. Fifty samples were prepared and classified as SC (self-curing acrylic resin), WB (heat-cured acrylic resin), ME (acrylic resin polymerized by microwave energy), P (resin print), and M (polymethylmethacrylate polymer block for computer-aided design/computer-aided manufacturing). The data were analyzed using a one-way analysis of variance and Tukey’s honestly significant difference test. Surface roughness was the same in all groups. The surface hardness of group M was statistically superior. The samples from groups P and M had higher flexural strength than other samples. The modulus of elasticity of group SC was statistically lower than that of other groups. The mechanical properties of the materials used to make the occlusal plates differed, and group M achieved the best results in all analyses. Therefore, clinicians must consider the material used to manufacture long-lasting and efficient occlusal splints.
Keywords: Bruxism; Mechanical Tests; Occlusal Splints